Exploring the potential impacts of anthropogenic heating on urban climate during heatwaves - Ansar Khan; Konstantina Vasilakopoulou; Mattheos Santamouris (Scientific Reports)
Abstract This study modeled the impact of anthropogenic heat (AH) on urban climates, focusing on Sydney during 2017’s heightened temperatures. The motivation behind this study stems from the increasing significance of understanding urban heat dynamics as cities globally grapple with regional climate change, necessitating targeted strategies for effective climate resilience cities. By investigating how varying levels of AH influence local urban climate conditions, this study addresses a critical gap in current urban climate study, particularly in the context of Sydney, an area that has not yet been extensively explored. Utilizing the weather research and forecasting (WRF) model coupled with building effect parameterization (BEP) and building energy model (BEM), i.e., the WRF/BEP + BEM model, four AH release scenarios were analyzed. Higher AH levels, especially at 14:00 LT, exhibited significant peaks: 266.5 W m−2 for sensible heat and 35.3 W m−2 for latent heat compared to the control scenario. This increase corresponded to a notable rise in ambient temperatures by 2.1 °C, with surface temperatures surging by 8.1 °C. Wind speeds notably increased by 4.6 m s−1 during higher AH release periods, affecting city airflow patterns. Moreover, elevated AH levels amplified the convective planetary boundary layer (PBL) height by 2013.7 m at 14:00 LT, potentially impacting pollutant dispersion and atmospheric quality. Notably, heightened AH profiles intensified sea breeze circulations, particularly impacting densely populated urban areas. These findings demonstrate a direct link between AH, exacerbated local urban warming, altered boundary layer dynamics, and intensified sea breeze circulations. This study emphasizes the urgent need to comprehend and manage AH for sustainable urban development and effective climate resilience strategies in Sydney and similar urban environments. By shedding light on these relationships, this study aims to contribute to the formulation of policies that mitigate urban overheating and enhance the livability of urban areas.